SLEEP HYGIENE AS AN IMPORTANT FACTOR IN MAINTAINING STUDENTS' HEALTH AND PERFORMANCE - Niyazova O. A.; Mirzaev Sh. T. (Web of Journals Publishing, 2026)
A survey was conducted to examine the relationship between sleep quality and student academic performance, which will allow for the development of recommendations for improving sleep and learning. In this article, we used The Pittsburgh Sleep Quality Index is a widely used instrument for quantifying sleep. In this study, sleep was assessed among 100 students using a digital version of the PSQI questionnaire. The main causes of sleep disturbances in students were identified.
Keywords: Sleep, sleep hygiene, Pittsburgh Sleep Quality Index ( PSQI ).